TEKNIK ANALISIS REGRESI LINEAR BERGANDA DAN IMPORTANT PERFORMANCE ANALYSIS UNTUK MENGUKUR TINGKAT KEPUASAN MAHASISWA TERHADAP KINERJA LAYANAN AKADEMIK - Ari Muhardono; Dwi Susilo (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2019)
One indicator of the success of managing a college is student satisfaction with the services carried out by the college in academic learning services and academic administration services.This research is a descriptive study that aims to find out how much the level of student satisfaction with the services carried out in the academic field both educators and education staff at the Faculty of Economics, Pekalongan University. This study uses data analysis techniques of Multiple Linear Regression and Importance Performance Analysis (IPA). Multiple linear regression is used to determine the direction of the relationship between the independent variable and the dependent variable, while the Importance Performance Analysis (IPA) is used to determine the level of student satisfaction with academic services by measuring the level of importance and level of implementation.Data obtained from questionnaires distributed to students using the dimensions of performance appraisal and expectations namely Tangible (physical evidence), Reliability (reliability), Responsiveness (responsiveness), Assurance (assurance), and Emphaty (empathy).The results showed that Performance and Expectations had a significant effect on Student Satisfaction. The results of the calculation of the student satisfaction index value of 0.70 it can be concluded that overall students of the Faculty of Economics, Pekalongan University feel